A hybrid deterministic–stochastic model for spouted beds - Golshan, Shahab; Zarghami, Reza; Mostoufi, Navid (Particuology, 2019)
[Display omitted] •A new hybrid stochastic–deterministic algorithm was proposed for simulation of spouted beds.•MC–DEM and CFD–DEM simulations of a slot-rectangular spouted bed were performed.•Proposed MC–DEM algorithm illustrated acceptable accuracy comparing to experiments.•Effects of cell size and sampling frequency were investigated on the performance of MC–DEM. A new hybrid deterministic–stochastic model is developed and used to simulate a slot-rectangular spouted bed. The model includes deterministic and stochastic steps that are executed in turn. The simulation starts with the deterministic part of the model, in which the computational fluid dynamics–discrete element method (CFD–DEM) equations are solved for 1s to give the initial velocity distribution of the particles. The stochastic part is then executed, with the hydrodynamics of the bed taken from the velocity distributions acquired in the first step through Monte Carlo sampling. A full deterministic (CFD–DEM) simulation of the bed is also conducted for comparison with the proposed hybrid model. Additionally, the proposed hybrid is validated using experimental data from the literature. These validations are based on the axial and lateral velocity distributions of the particles and the bed voidage. The effects of the cell size and number of sampling steps on the accuracy of the model are also investigated. The performance of the proposed model is compared with the CFD–DEM results in terms of the computation time and the rate of solid circulation in the bed. The hybrid model is found to have shorter runtimes than the CFD–DEM approach.